Control and analysis of simulator and biological data from car simulators - Volf, Petr; Hejda, Jan; Bernášková, Kristýna; Francová, Anna; Hýbl, Ján; Hourová, Michaela; Kutílek, Patrik (Lékař a technika, 2021)
Due to the fact that driving vehicles can be complicated or impracticable, a computer simulator is usually used for training and professional studies. The advantage of this approach is high safety, repeatability, easier feasibility and, of course, lower price. In this work we describe the extension of the car simulator developed by the Faculty of Transport CTU in Prague with specific scenarios for evaluating the cognitive abilities of probands, software for their management and evaluation of data from simulator software and other measured physiological variables such as ECG and arm movement. From the data it is then possible to evaluate the mental and physical condition of the proband and the progress of training. Preliminary results suggest the possibility of using Poincaré analysis for the purpose of assessing cognitive load during potential collision situations. It uses distance assessment from other objects involved in traffic situations.
Keywords: automobily; Computer Simulation; Biomedical Research; počítačová simulace; Electrocardiography; Work Capacity Evaluation; posuzování zdravotní způsobilosti; Automobiles; řízení motorových vozidel; biomedicínský výzkum; lidé; Automobile Driving; Humans; elektrokardiografie